2020
DOI: 10.3390/su12072769
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Decision Support Model for Eco-Friendly Material Selection in Vietnam

Abstract: In recent years, the awareness of sustainable construction has increasingly risen in countries around the world, with the main goal being to avoid depleting energy resources and raw materials and to greatly reduce carbon emissions. Therefore, the selection of eco-friendly building materials becomes a difficult task and choosing the best construction strategy is a complicated process. Most of the studies of the building material selection often focus on optimizing material-related green building scores with bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…As a material selection model similar to this study, there existed a local model in Vietnam and a model for the LEED score. Vietnam's model created a model that considers both the number of working days and the cost of materials to meet the minimum cost to receive a score for certification [22]. In the study of the model for selecting materials for LEED, a model was developed to derive a material proposal that satisfies the optimal material alternative for obtaining a score at a minimum cost [23,24].…”
Section: Existing Research Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a material selection model similar to this study, there existed a local model in Vietnam and a model for the LEED score. Vietnam's model created a model that considers both the number of working days and the cost of materials to meet the minimum cost to receive a score for certification [22]. In the study of the model for selecting materials for LEED, a model was developed to derive a material proposal that satisfies the optimal material alternative for obtaining a score at a minimum cost [23,24].…”
Section: Existing Research Reviewmentioning
confidence: 99%
“…In this way, many studies have been conducted through their methods on optimizing the cost of obtaining LEED scores and obtaining the least-cost materials for obtaining the scores [23,24]. In particular, in Vietnam, new factors are being considered, such as developing a model that considers labor according to materials [22]. However, researchers in Korea have so far primarily proposed improvements to the G-SEED certification system by analyzing and comparing the limitations of the current G-SEED system to those of foreign institutions.…”
Section: Research Significancementioning
confidence: 99%
“…Usage of the solar panel [3,4,7] 5. Usage of low VOC paint [39][40][41] 5. Usage of EnergyStar appliances [42] 4.…”
Section: Environment Enhancement Evaluation Factorsmentioning
confidence: 99%
“…Effective air circulation can reduce emissions from VOC. Previous studies suggested the utilisation of VOC paint should be no more than 30 mg/L [40,41].…”
Section: Technical Solution As Decision Alternativesmentioning
confidence: 99%
“…In ASEAN, green material and green building are the common key terms to build a green environment and have sustainable construction. Green building is refer to utilization of green materials that are environmentally friendly to reduce resources and construction waste [4]. Green materials are renewable materials and the impact of material is considered throughout its life cycle [5].…”
Section: Introductionmentioning
confidence: 99%